Monthly Rainfall and Severity of Melioidosis in Nakhon Phanom, Northeastern Thailand - Tanwisaid, Kittisak; Surin, Uraiwan (Journal of Health Science of Thailand, 2017)
In a 6-year retrospective analytical study, 340 culture-confirmed cases of melioidosis with an average annual prevalence of 9.97/100,000 fromNakhonPhanomHospital, Northeast of Thailand were included. The total monthly rainfall data was significantly linear correlated with number of patients with melioidosis in the years 2001-2006 [(r = 0.633, p < 0.05), (r = 0.622, p < 0.05), (r = 0.804, p <0.01), (r =0.734, p < 0.01), (r = 0.844, p <0.01), (r =0.884, p < 0.01) respectively]. The 73.27 percent of the patients were affected in the rainy season (June to November). Admitted 321 cases affected all ages with the highest incidence in 41-60 years group (51.71%). The 72.27 percent of the cases had underlying diseases. The common risk factors included diabetes mellitus or chronic renal disease. The mainly clinical presentations were pneumonia (30.84%) and sepsis with bacteremia (30.22%). Overall mortality was 43.61 percent but mortality in proper antibiotic treatment cases was 32.57 percent. On multivariate regression analysis, the independence risk factors of case-fatality significantly associated with acute respiratory failure: adjusted odd ratio 21.83(95%CI 8.09,58.92) p<0.001, septic shock 4.39(1.77,10.87) p<0.01, non proper antibiotic treatment cases 3.20(1.34,7.63) p<0.01, tachycardia 2.69(1.20,6.07) p<0.05, white blood cell count <5,000 cells/mm3 6.85(1.84,25.42) p<0.01, platelet count <100,000 cells/mm3 3.78(1.59,9.03) p<0.01, band form of polymorphonuclear ณ 1% 3.67(1.75,7.72) p<0.01, NaHCO3 <15 meq/L 3.59(1.81,7.14) p<0.001. Melioidosis is an important infectious disease in Northeast of Thailand showing very high prevalence in Nakhon Phanom province ralative to other regions inThailand. Rapid diagnosis and proper management of high risk cases can decrease morbidity and mortality. Studies exploring the role of preventive measures and earlier clinical identification in rainy season are required to reduce the burden of this disease.